An Efficient Assistive Solution for Elderly Dementia Care - Jeeva, A.; Gayathri, K.; Arulselvi, S.; Rajesh, K. (International Journal of Engineering and Technology, 2018)
Aging population is becoming a major concern of human society in the recent years. Elderly people suffering from Alzheimer and dementia have cognitive declines making them difficult in remembering landmarks in their outdoor navigational tasks. Therefore, disorientation and wandering become common for elderly people even in their familiar environments. Providing assistive guidance to such elders is a challenging task for caretakers as most of the elders prefer to live independently. Thus, there arises a need for detecting the disorientation of the elders in their outdoor navigation and alerting the caretakers in the account of either disorientation or wandering being detected. Further, elderly people can be provided with navigational assistance by mining through their previous historical trajectories and suggesting a location to which the elder has frequently visited at the time when the disorientation had been detected. In addition, a tool can be developed to analyse the level of cognitive decline by identifying the frequencies of different types of wandering patterns that might help to provide effective medication in the treatment of cognitive decline and guidance.Â Â